Factors influencing health behaviours among Malaysia university students in a Malaysian public university - Omar Dev, Roxana Dev; Tengku Kamalden, Tengku Fadilah; Soh, Kim Geok; Abdullah, Maria Chong; Mohd Ayub, Ahmad Fauzi; Ismail, Ismi Arif (Institut Penyelidikan Pembangunan Belia Malaysia, Kementerian Belia dan Sukan Malaysia, 2018)
University students typically enter a dynamic transitional period of new independence from their parents that is characterized by many factors. These factors which involve social, financial, and environment elements, can be a burden to the students putting them at risk in negative health behaviours. Negative health behaviours among university students are a course of concern since they have a tendency to be carried into adulthood which can possibly cause the emergence of chronic disease at younger age. Self-efficacy is seen to increase with students’ emotional intelligence, together with better health behaviour. Therefore, the purpose of the study was to investigate the relationship between emotional intelligence and self-efficacy (mediator) on health behaviours among university students in Universiti Putra Malaysia, Malaysia. A correlational study was conducted on 400 undergraduates university students who lived on campus and were chosen through stratified random sampling technique using closed ended questionnnaires (Schutte’s Self Report Emotional Intelligence, General Self Efficacy Scale and a modified version of Health Style Questionnaire). Emotional intelligence, self-efficacy and health behaviour were significantly correlated at p <.05. Thus, there was an association between emotional intelligence and self-efficacy with health behaviour. Emotional intelligence and self-efficacy can boost positive health behaviour Such data have important implications for both health practice and policy especially for higher education institutions.